Faktor yang berhubungan dengan Status Gizi Bayi Usia 0–12 Bulan di Posyandu Dahlia Palembang - Yulvira Febriani; Annisa Khoiriah; Maya Erisna (Jurnal Kebidanan Harapan Ibu Pekalongan, 2026)
Infant nutritional problems remain a public health concern as they affect child growth and development. Infant nutritional status is influenced by various factors related to infant characteristics and family conditions. This study aimed to identify factors associated with the nutritional status of infants aged 0–12 months at Dahlia Integrated Health Post, Palembang. This quantitative study employed a cross-sectional design. The population included all infants aged 0–12 months, with a total sampling technique resulting in 30 infants. Independent variables included infant age, sex, birth weight, exclusive breastfeeding, maternal education, maternal occupation, and parental income. Nutritional status was assessed using weight-for-age, length-for-age, and weight-for-length indicators. Data were analyzed using Chi-Square and Fisher’s Exact tests. The results showed that most infants had normal nutritional status based on all anthropometric indicators. Bivariate analysis indicated no significant association between most infant and family factors and nutritional status. However, infant age was significantly associated with nutritional status based on length-for-age (p < 0.05). These findings highlight the importance of early monitoring of linear growth in infants, particularly during the complementary feeding transition period.